A review of leading COVID-19 vaccines, the quest for immune protection, and its key challenges. Part 3: Covid-19 vaccines – Key challenges and translational science - Hartshorne, Johan; Villiers, Pierre (My University, 2021)
Rationale • Developing and deploying safe and effective COVID-19 vaccines are faced with many challenges and unanswered questions. • Massive amounts of heterogenic scientific data are being generated that are needed rapidly to advance vaccine development, protect people and restore normality. • The purpose of Part 3 of this four-part series is to review the scientific considerations related to key challenges associated with COVID-19 vaccines and immune protection with the focus of making this data more meaningful and open for clinicians. Key points • The primary immunogen (antigen) required to induce neutralising antibodies (humoral) and T cell (cellular) immune responses is the S-protein fragment of SARS-CoV-2. • Currently, the evidence is firmly pointing towards neutralising antibodies, being more critical for protection. • Long-term protective or durable immune memory is driven by virus-specific T cell and B cell responses (adaptive immunity). • Circulating antibody titres are not predictive of T cell immune memory. • Durable immune memory is a crucial factor to sustain herd immunity. • Adjuvants are added to certain vaccines to provoke a more robust and durable immune response. • Adjuvants that provoke TH1-biased immune responses are preferred. • 90% of adults are seropositive for 'common cold' CoV strains. • There is a cross-reactivity between specific T cell of SARS-CoV-2 and 'common cold' CoV's. • Prior infection with 'common cold' can play a potentially protective role. • Seropositive individuals present with a rapid and higher antibody immune response after a single dose with an mRNA vaccine. • Vaccine-induced immune responses resulting in non-neutralising antibodies, low antibody titres, and abnormal T cell responses (TH2- biased) are potential risks for serious enhanced disease events but unlikely events. • Vaccine strategies aimed at inducing high titres on neutralising antibodies and TH1- biased immune responses reduce the risk of serious adverse events. • Emerging variants of concern are extremely infectious, highly transmissible and threatens the protective efficacy of current vaccines. Public health implications • A rapid global vaccination campaign combined with standard mitigation measures to stop transmission is the best defence against the emergence of further SARS-CoV-2 variants and the safest way to attain herd immunity. • Booster immunisations may be required to promote or improve the durability and strength of vaccine immunity.
Keywords: adjuvants; coronavirus; COVID-19 vaccines; herd immunity; immune escape; immune memory; immunogen; neutralising antibodies; SARS-CoV-2 variants; vaccination; vaccine-induced disease